Species Selection for Profitable Commercial Fish Culture Through Biofloc Technology - Kamruzzaman; Laboni, Taiba Akter Laboni; Khatun, Mst Shahinur Khatun; Rahman, Obaidur Rahman; Rahman, Md Mahabubur Rahman; Ilah, Nur E Farjana Ilah; Abedin, Md Joynal Abedin; Rahman, Md Ashekur Rahman; Md Harun; Hasan, Md Mahmudul Hasan; et al. (Journal of Bio-Science, 2023)
Biofloc technology is a recent concept in Bangladesh, it has numerous advantages for enhancing aquaculture production in several countries, thereby contributing to achieve sustainable development goals. To identify the most suitable fish species for profitable commercial fish culture through Biofloc, a 100-day experiment was conducted at Pran Fisheries Project in Razapur Village, situated in Sreemangal Upazilla of Moulvibazar district, commencing in March 2021. The experiment comprised three treatments: Oreochromis niloticus, Anabus testudineus, and Labeo rohita with two replicates for each treatment. Water quality parameters were meticulously monitored to ensure optimal conditions. All treatments were conducted at a temperature of 26°C, with pH levels of 7.6-7.8, dissolved oxygen concentrations of 5-6 ppm. During the study, O. niloticus exhibited the highest body weight (66.23 ± 0.94) compared to A. testudineus (50.82 ± 0.94) and L. rohita (53.92 ± 0.17). Furthermore, L. rohita displayed a higher average daily weight gain (1.8 ± 0.003) and specific growth rate (3.29 ± 0.29). The best feed conversion ratio (FCR) was observed both for O. niloticus (0.98 ± 0.33) and A. testudineus (0.98 ± 0.03). In terms of survival rate, O. niloticus outperformed the other species, with a rate of 98%. However, O. niloticus demonstrated better aquaculture performance compared to the other species using biofloc technology. This research provides valuable insights in effective cultural techniques that can enhance fish production through biofloc technology, contributing to economic growth in aquaculture sector and national development. J. Bio-Sci. 31(1): 71-85, 2023